Immune modulation as a consequence of SARS-CoV-2 infection - Gelmez, Metin Yusuf; Oktelik, Fatma Betul; Tahrali, Ilhan; Yilmaz, Vuslat; Kucuksezer, Umut Can; Akdeniz, Nilgun; Cetin, Esin Aktas; Kose, Murat; Cinar, Cigdem; Oguz, Fatma Savran; Besisik, Sevgi; Koksalan, Kaya; et al. (Frontiers in Immunology, 2022)
Erroneous immune responses in COVID-19 could have detrimental effects, which makes investigation of immune network underlying COVID-19 pathogenesis a requisite. This study aimed to investigate COVID-19 related alterations within the frame of innate and adaptive immunity. Thirty-four patients clinically diagnosed with mild, moderate and severe COVID-19 disease were enrolled in this study. Decreased ILC1 and increased ILC2 subsets were detected in mild and moderate patients compared to healthy controls. NK cell subsets and cytotoxic capacity of NK cells were decreased in severe patients. Moreover, CD3+ T cells were reduced in severe patients and a negative correlation was found between CD3+ T cells and D-dimer levels. Likewise, moderate and severe patients showed diminished CD3+CD8+ T cells. Unlike T and NK cells, plasmablast and plasma cells were elevated in patients and IgG and IgA levels were particularly increased in severe patients. Severe patients also showed elevated serum levels of pro-inflammatory cytokines such as TNF-α, IL-6 and IL-8, reduced intracellular IFN-γ and increased intracellular IL-10 levels. Our findings emphasize that SARS-CoV-2 infection significantly alters immune responses and innate and acquired immunity are differentially modulated in line with the clinical severity of the disease. Elevation of IL-10 levels in NK cells and reduction of CD3+ and CD8+ T cells in severe patients might be considered as a protective response against the harmful effect of cytokine storm seen in COVID-19.